2019
DOI: 10.1111/ejh.13237
|View full text |Cite
|
Sign up to set email alerts
|

The role of long non‐coding RNAs in multiple myeloma

Abstract: Multiple myeloma (MM) is still an incurable disease, and its pathogenesis involves cytogenetics and epigenetics. In recent years, the roles of long non‐coding RNAs (lncRNAs) in MM have been deeply studied by scholars. LncRNAs are defined as a class of non‐protein‐coding transcripts greater than 200 nucleotides in length, which are involved in a large spectrum of biological processes, including proliferation, differentiation, apoptosis, invasion, and chromatin remodeling. However, little is known about the spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 94 publications
(144 reference statements)
0
19
0
Order By: Relevance
“…10 They are involved in several aspects of physiological and pathological processes, and their regulatory functions are mediated via diversified mechanisms involving chromatin modification, gene transcriptional regulation, epigenetic modulation, mRNA post-transcriptional processing, and interaction with proteins or microRNAs (miRNAs). [11][12][13] In recent years, alteration of lncRNA expression has been widely reported in numerous human malignancies and is likely to exert a great impact on carcinogenesis and cancer progression. [14][15][16] Regarding OS, extensive evidence has demonstrated that many lncRNAs are dysregulated and that this dysregulation is important in tumor onset and development.…”
Section: Introductionmentioning
confidence: 99%
“…10 They are involved in several aspects of physiological and pathological processes, and their regulatory functions are mediated via diversified mechanisms involving chromatin modification, gene transcriptional regulation, epigenetic modulation, mRNA post-transcriptional processing, and interaction with proteins or microRNAs (miRNAs). [11][12][13] In recent years, alteration of lncRNA expression has been widely reported in numerous human malignancies and is likely to exert a great impact on carcinogenesis and cancer progression. [14][15][16] Regarding OS, extensive evidence has demonstrated that many lncRNAs are dysregulated and that this dysregulation is important in tumor onset and development.…”
Section: Introductionmentioning
confidence: 99%
“…LncRNAs are deregulated in many human cancers and are associated with disease progression [ 9 , 10 , 11 ]. Several studies, including ours, have shed light on the role of lncRNAs in MM progression [ 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the accumulating evidence of their important role in MM, at present only a few of these lncRNAs have been individually investigated to determine to what extent and by what molecular pathways they influence MM cell growth, tumour progression, treatment-response and disease outcome. Among the few lncRNAs which have been extensively investigated in MM, important examples include the well-established oncogenic lncRNAs MALAT1, H19, TUG1, UCA1 as well as the known tumoursuppressor lncRNA MEG3 (for recent reviews see [21][22][23]). Importantly, these studies revealed that lncRNAs often affect MM cell growth and tumour progression by different pathways to those observed in other malignancies, suggesting that the molecular mechanisms involved are likely to be disease-and context-dependent.…”
Section: Long Noncoding Rnas In Multiple Myelomamentioning
confidence: 99%